Renal solute load in preterm infants. Issue 4 (April 1990) - De Curtis, M; Senterre, J; Rigo, J
Abstract : We performed metabolic balance studies in 77 preterm infants fed on human milk or adapted formulas, to determine the renal solute load and compared it with the potential renal solute load estimated by the composition of the diet or the urine according to Ziegler's, Bergman's, and Shaw's calculations. The renal solute load found in preterm infants was lower than that observed in young full term infants. Although all calculations predicted the renal solute load well, the equation proposed by Ziegler and Fomon from dietary protein and electrolyte load appears to be the simplest to calculate renal solute load accurately in preterm infants.